The Impact of Digital Era Transformation on Human Resource Management - Zakaria, Endang; Hadiyan, Hadiyan; Lawrence, Lucas (Pandawan, 2025)
Significant changes have been brought about by the digital age in many areas of business, including human resource management (HRM). The significant effects of digitalization on HRM strategies, practices, and organizational dynamics are examined in this research. This study explores how technological innovations such as automation, big data analytics, and artificial intelligence have transformed traditional HRM functions and processes. Through a thorough analysis of relevant literature, the research highlights how the advent of digital technologies has reshaped recruitment and talent acquisition. The integration of digital tools enables HR managers to efficiently find, attract, and retain top talent by leveraging online platforms, social media, and data-driven insights. Moreover, HR procedures like performance management, training and development, and employee engagement have been optimized, resulting in greater efficiency and productivity in the workplace. Furthermore, the adoption of digitalization supports data-driven decision-making and enhances employee experiences through personalized solutions. This transformation aligns HRM practices with the evolving technological landscape, positioning organizations to meet the dynamic demands of the modern workforce. In conclusion, digitalization has fundamentally reshaped HRM, offering innovative strategies to manage human capital effectively in the digital era.